Vitrectomy with a modified temporal inverted limiting membrane flap to reconstruct the foveolar architecture for macular hole retinal detachment in highly myopic eyes. Issue 1 (5th July 2017) - Ho, Tzyy‐Chang; Ho, Allen; Chen, Muh‐Shy
Abstract: Purpose: We investigated the surgical results of macular hole retinal detachment (MHRD) with a modified C‐shaped temporal inverted internal limiting membrane (ILM) flap to reconstruct the foveolar architecture in highly myopic eyes. Methods: Eighteen highly myopic eyes with MHRD in 17 patients who underwent a vitrectomy with a modified C‐shaped temporal inverted ILM flap were followed for 12 months. Anatomic outcomes were evaluated by fundus examinations and optical coherence tomography. The preoperative and postoperative best‐corrected visual acuities (BCVAs) were compared as functional outcomes. Results: Women accounted for 88% of the MHRD patients. The mean age was 60.2 ± 8.2 years. The mean axial length was 29.25 ± 2.10 mm. Type 1 and type 2 MHRD was present in four eyes and 14 eyes, respectively. After a single surgery, the hole was closed in 18 eyes (100%). Retinal attachment was achieved in 95%. Persistent shallow subretinal fluid (SRF) was noted in one case, which was resolved at follow‐up. The surgery significantly improved BCVAs (from 1.7 ± 0.6 to 0.72 ± 0.4 logarithm of the minimum angle of resolution units [p < 0.001]) at the last visit. In total, 94.4% of the eyes had restored foveolar architecture. Ellipsoid zone recovery within the foveola was found in 77.8% of the eyes. Conclusion: A vitrectomy and modified C‐shaped inverted temporal ILM flap is effective for closing MHs, reattaching the retina, restoring the foveolar architecture and significantly improving the postoperative BCVA in MHRD patients. This technique is feasible, and we propose 'presumed' Müller cell cone repair in MHRD surgery.